Understanding Memayu Hayuning Saliro teachings and internal locus of control on students’ interest in investing in the capital market - Dewi Kusuma Wardani; Nugroho, Fajar Adi (Proceeding International Conference on Accounting and Finance, 2024)
The aim of this research is to investigate the impact of Memayu Hayuning Saliro’s teachings and the role internal control plays in students’ interest in capital market investing. Quantitative research methodology is applied. Data collection is done using a google form, and data analysis is done using the SPSS 23.0 application. The study’s findings demonstrate that knowledge of Memayu Hayuning Saliro’s teachings has no effect on students’ interest in making capital market investments; this is supported by the significance value of Memayu Hayuning Saliro, which is 0.205 > 0.05 and 1.274 < 1.980, meaning that the value of B indicates a positive number, namely 0.71. Furthermore, students’ interest is impacted by their comprehension of the internal locus of control.